La gimnasia cerebral para desarrollar la atención en los niños de preparatoria de la unidad educativa “Manuel Ignacio montero Valdivieso” de la ciudad de Loja, en el período 2019-2020. - Cango Dávila, Karen Andrea (2021)
The present investigation is directed to as the cerebral gymnastics develop the attention in the children of Preparatory of the Educational Unit “Manuel Ignacio Montero Valdivieso”; having like general target, to determine like the cerebral gymnastics helps to develop the attention in the children of Preparatory. The research design is experimental, the used methods were: scientific, analytical-synthetic, inductive-deductive, statistical-descriptive; for the information securing one interviewed the classroom teacher, and the used Instrument was the Guide of Evaluation for the Attention, the population belonged to 52 persons, taking a sample not probabilistic of 20 children and 1 teacher. The results of the diagnosis of the Global Attention determined that 65%of the students had problems of attention, being located in a scale of severe and critical, to contribute to the development of the attention, a so called alternative proposal was applied “Attending to the world across the movement”, based on activities of cerebral gymnastics together with activities related to every type of attention, where the obtained results demonstrate a big advance, 65 % of the children does not present problems of attention; 30 % presents a problem attentional lightly. Concluding that the cerebral gymnastics contribute significantly to the development of the attention, which one is a methodological tool that must be implemented inside the pedagogic planning.